A Case Study of Teaching Speaking Skills in Large Classes: Problems and Solutions - Bhutto, Alia Ali; Jokhio, Amjad Ali; Ahmad, Asif (Pakistan Journal of Humanities and Social Sciences, 2023)
Class size is a major concern at any educational setup. However, when we talk about large classes, its notion varies from country to country and context to context. There is no exact quantitative definition of what means a large class does not have the exact size; it is measured by number of students per teacher, and various perceptions teachers have regarding the large classes in their teaching and learning context, issues, challenges, classroom management strategies, assessment and feedback methods and recommendations, etc. This study investigates the teachers’ perception of teaching speaking skills in large classes, various issues and strategies. There is substantial research evidence that teaching speaking skills in large classes contribute significant challenges for both, teachers and students. However, when some professional and experienced teachers used large classroom teaching strategies and speaking activities, practicing speaking skills was no more a challenge for them. They also enjoyed teaching speaking in large classes via various classroom management techniques, strategies, activities and through standard speaking lesson plan. The study followed a qualitative research paradigm. A case study with detailed semi-structured interviews was used to precede the research. A sample of 15 English Language Teachers (ELTs) as research participants were selected from different public and private sector universities of Karachi. Interviews were transcribed first than initial and focus coding and themes were generated for open ended questions. The major themes were related to the issues/ challenges, classroom management strategies, assessment and feedback methods and recommendations of teaching speaking skills in large classes.